2019
DOI: 10.1016/j.omto.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Histone Methyltransferase DOT1L by a Novel Psammaplin A Analog Inhibits Growth and Metastasis of Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is the most intractable cancer in women with a high risk of metastasis. While hyper-methylation of histone H3 catalyzed by disruptor of telomeric silencing 1-like (DOT1L), a specific methyltransferase for histone H3 at lysine residue 79 (H3K79), is reported as a potential target for TNBCs, early developed nucleoside-type DOT1L inhibitors are not sufficient for effective inhibition of growth and metastasis of TNBC cells. We found that TNBC cells had a high expression level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Total cell lysates were mixed with lysis buffer, and boiled for 10-20 min at 100°C. The protein concentrations of the cell lysates were determined by the BCA protein assay ( Byun et al ., 2019 ). Samples containing equal amounts of protein were subjected to SDS-polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Total cell lysates were mixed with lysis buffer, and boiled for 10-20 min at 100°C. The protein concentrations of the cell lysates were determined by the BCA protein assay ( Byun et al ., 2019 ). Samples containing equal amounts of protein were subjected to SDS-polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings suggested that the inhibitory effect of NepA on the production of SAM via the inhibition of SAH might also affect the histone methylation status of human cancer cells. In BC, the upregulated methylation of H3K79 (H3K79me) is known to be correlated strongly with a poor clinical outcome [2]. Therefore, we focused on DOT1L expression and DOT1L-mediated methylation levels in BC cells.…”
Section: Expression Levels Of Dot1l and Antiproliferative Activities mentioning
confidence: 99%
“…Breast cancer (BC) is the most commonly occurring cancer and second leading cause of cancer-related death in women worldwide [1,2]. Chemotherapy, radiation therapy, and surgical options such as mastectomy or lumpectomy have been identified as the most effective and common strategies for the treatment of early-stage BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each protein was subjected to 6-15% SDS-PAGE. Proteins were transferred onto PVDF membranes (Millipore, Bedford, MA, USA) by electroblotting, and membranes were blocked for 1 h with blocking buffer [5% bovine serum albumin (BSA) in tris-buffered saline-0.1% Tween 20 (TBST)] at room temperature [38]. Membranes were then incubated with indicated antibodies (mouse anti-β-actin, diluted 1:10,000; other antibodies, diluted 1:500-1:1000 in 5% BSA/TBST) overnight at 4 • C and washed three times for 10 min with TBST.…”
Section: Western Blot Analysismentioning
confidence: 99%